Oscillation, synchrony, and multi-factor patterns between cereal aphids and parasitoid populations in southern Brazil. Issue 2 (6th April 2022) - Engel, Eduardo; Lau, Douglas; Godoy, Wesley A. C.; Pasini, Mauricio P. B.; Malaquias, José B.; Santos, Carlos D. R.; Pivato, Juliana; Pereira, Paulo R. V. da S.
Abstract: In different parts of the world, aphid populations and their natural enemies are influenced by landscapes and climate. In the Neotropical region, few long-term studies have been conducted, maintaining a gap for comprehension of the effect of meteorological variables on aphid population patterns and their parasitoids in field conditions. This study describes the general patterns of oscillation in cereal winged aphids and their parasitoids, selecting meteorological variables and evaluating their effects on these insects. Aphids exhibit two annual peaks, one in summer–fall transition and the other in winter-spring transition. For parasitoids, the highest annual peak takes place during winter and a second peak occurs in winter–spring transition. Temperature was the principal meteorological regulator of population fluctuation in winged aphids and parasitoids during the year. The favorable temperature range is not the same for aphids and parasitoids. For aphids, temperature increase resulted in population growth, with maximum positive effect at 25°C. Temperature also positively influenced parasitoid populations, but the growth was asymptotic around 20°C. Although rainfall showed no regulatory function on aphid seasonality, it influenced the final number of insects over the year. The response of aphids and parasitoids to temperature has implications for trophic compatibility and regulation of their populations. Such functions should be taken into account in predictive models.